Islam as a unifying force in Somali politics - Shuriye, Abdi Omar (International Institute for Muslim Unity, International Islamic University Malaysia, 2006)
This paper contends that Islam remains to be the unifying factor in Somali politics. Substantiations of this discernment are traced from the history of Somali politics and the role played by Islam. A preliminary sketch of the political history of Somali Islam is necessary to establish the position of Islam. This endeavor, however, ventures to conceptualize the current state of affairs, as it aims to identify the political ideals of this government-phobia nation.